2021
DOI: 10.1155/2021/5593608
|View full text |Cite
|
Sign up to set email alerts
|

What Is in the Field for Genetics and Epigenetics of Diabetic Neuropathy: The Role of MicroRNAs

Abstract: Despite the high prevalence of diabetic neuropathy, its early start, and its impact on quality of life and mortality, unresolved clinical issues persist in the field regarding its screening implementation, the understanding of its mechanisms, and the search for valid biomarkers, as well as disease-modifying treatment. Genetics may address these needs by providing genetic biomarkers of susceptibility, giving insights into pathogenesis, and shedding light on how to select possible responders to treatment. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Genetic research in this field mainly aims to find genetic alterations, variants, or biomarkers associated with an increased risk of developing DPN, to give insights into the pathogenesis, and to find responders to treatment [ 57 ]. Moreover, researchers have paid attention to the possible role of miRNAs, small gene regulators, in the development of diabetes and its micro- and macrovascular complications [ 58 ].…”
Section: Pathophysiology Of Peripheral Neuropathy In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic research in this field mainly aims to find genetic alterations, variants, or biomarkers associated with an increased risk of developing DPN, to give insights into the pathogenesis, and to find responders to treatment [ 57 ]. Moreover, researchers have paid attention to the possible role of miRNAs, small gene regulators, in the development of diabetes and its micro- and macrovascular complications [ 58 ].…”
Section: Pathophysiology Of Peripheral Neuropathy In Diabetesmentioning
confidence: 99%
“…Moreover, researchers have paid attention to the possible role of miRNAs, small gene regulators, in the development of diabetes and its micro- and macrovascular complications [ 58 ]. For what concerns genes, a role of such as angiotensin converting enzyme (ACE) gene, methylenetetrahydrofolate reductase (MTHFR) gene, glutathione peroxidase-1 (GPx-1) gene, catalase (CAT) gene, and genes associated with the pentose phosphate pathway has been proposed [ 57 ]. Human studies have explored the association between miRNAs and the development of DPN.…”
Section: Pathophysiology Of Peripheral Neuropathy In Diabetesmentioning
confidence: 99%
“…V. Spallone et al summarized the results of animal and human studies linking microRNAs (miRNAs) to diabetic neuropathy, and explored the possible pathogenic significance of these associations, especially with regard to miR-128a, miR-155a and miR-499a, and their application in the screening of diabetic neuropathy. The authors found that the miRNA gene polymorphism is closely related to diabetic neuropathy [ 104 ]. Axon degeneration is the main pathological feature of many early peripheral neuropathies, including diabetic neuropathy.…”
Section: Obesity-associated Diabetes and Neurological Diseasesmentioning
confidence: 99%
“…miR-155 has been found to have a protective effect in animal studies, by improving insulin sensitivity. The difficulty of further implementing these observations consists of the poor understanding of the time periods in which detection could suggest early subclinical neuropathy [ 90 , 91 ]. Naturally, recent research has shown potential biomarkers for DM that act through their role in mediating inflammation through their axonal regenerative properties.…”
Section: The Association Of Specific Mirna With Diabetes Related Comp...mentioning
confidence: 99%
“…However, genetic studies conducted on several polymorphisms of miR146, 128 and 21a genes have concluded that these modifications might have an important role to play within the inflammatory and metabolic pathways that undergo in DN progression. Extensive research must be continued for a better understanding [ 88 , 89 , 91 ].…”
Section: The Association Of Specific Mirna With Diabetes Related Comp...mentioning
confidence: 99%